PENETRASI PRAKTIK ‘SHADOW BANKING’ DI INDONESIA - ROSALIA RACHMAWATI, IKA Rosalia (Jurnal Akuntansi AKUNESA, 2012)
These day the world of economy matters in Indonesia begins to recognize the technical term of shadow banking. Shadow banking is non-bank financial institution gives credit which conducts many operational activities proper with banks. Because this activity has unregulated and unsupervised firmly, it becomes significant to watch closely which potential causing many crisis at following term in Indonesia. The activities of shadow banking grow and substantiate penetration applied the gap of banking regulation which is stricter than shadow bank institutions. This paper proposes to analyze the influence of banking regulation on a practice of shadow banking and an impact of Indonesia economy. In using an explanatory research, the point of this research is that the regulation of industrial banking becomes strict, it shows that growing the gap of shadow banking institution for penetration makes use of banking regulation. The growth of unregulated shadow banking gives negative effect for economy stability of country.Keywords: shadow banking, bank regulation, bank